Influence of Staff Development Programmes on Staff Job Performance in Colleges of Education in North Eastern Nigeria (Global Journal of Human-Social Science, 2019)
The study was carried out to investigate staff development programmes on staff job performance in Colleges of Education in North Eastern Nigeria Two objectives were stated to guide the study which was translated into two research questions and two null hypotheses The study adopted a survey research design where the populations of the study were 9 847 academic and non-academic staff of Federal and State Colleges of Education A sample of 384 staff was sampled for the study using Taro Yamen s formula for sample size determination Multistage sampling technique which involves purposive random sampling technique and proportionate stratified sampling techniques were used to sample the staff respectively to avoid bias and to ensure fairness in sampling A self-structured questionnaire titled Staff Development Programmes and Staff Job Performance Questionnaire SDPSJPQ was used for data collection The data was collected by the researcher and the research assistant
Keywords: staff development programmes; staff job performance; orientation and mentoring